Investigating the relationship between financial technology on financial access in Cameroon: Emperical study - Eduke, Ekane Mirabelle; Guy, Omenguele Rene; Tambi, Mbu Daniel (Asian Journal of Empirical Research, 2025)
This empirical study aims to investigate the relationship between financial technology (FinTech) and financial access in Cameroon. With the increasing adoption of financial technology in the financial service sectors, it is essential to determine whether the use of these technologies has a significant impact on financial access. Methodologically, to appraise the link between FinTech and financial access, the study applied the autoregressive distributed lag (ARDL) technique. Data related to financial access were obtained from the Financial Development and Structural Dataset, while bank technological-related data, such as the Depth of Automatic Teller Machines (ATMs), were obtained from the International Monetary Fund (IMF) database. The ARDL Bounds Test results make a substantive contribution to the scholarly discourse by empirically affirming the existence of a long-term cointegration relationship between FinTech and financial access. The outcome shows that in the short run, FinTech has a positive effect on financial access up to the third lag, and the long-run outcome equally confirms a positive and significant effect of FinTech on financial access in Cameroon. In terms of policy recommendations, policymakers should implement programs that incorporate initiatives to promote FinTech, while consumers need to learn about the benefits of FinTech and how to use FinTech services safely.